Beyond resistance: The role of prefiguration in social movements addressing the climate crisis - Hamish Evans (University of Bath, Centre for Development Studies (CDS), 2021)
The concept of building alternatives through prefiguration has been applied to social movements, particularly in Latin America (Dinerstein 2014). This paper extends prefigurative analysis and praxis to the environmental movement, focusing on Extinction Rebellion in the UK. It builds on an emerging reframing of social movements as autonomies beyond resistance, encapsulating both creation and experimentation. On the relationship between oppositional activism and resistance, the paper points towards a necessary union of deconstructive and constructive work for 21st century social movements, to birth a new society in the shell of the old. This situates the adversarial and exemplary as synergies rather than trade-offs in the work of social change.
Keywords: 330; prefiguration; social movements; extinction rebellion; environment